Pathogenic variants in PLOD3 result in a Stickler syndrome-like connective tissue disorder with vascular complications. Issue 9 (25th May 2019) - Ewans, Lisa Jean; Colley, Alison; Gaston-Massuet, Carles; Gualtieri, Angelica; Cowley, Mark J; McCabe, Mark James; Anand, Deepti; Lachke, Salil A; Scietti, Luigi; Forneris, Federico; Zhu, Ying; Ying, Kevin; et al.
Abstract : Background: Pathogenic PLOD3 variants cause a connective tissue disorder (CTD) that has been described rarely. We further characterise this CTD and propose a clinical diagnostic label to improve recognition and diagnosis of PLOD3 -related disease. Methods: Reported PLOD3 phenotypes were compared with known CTDs utilising data from three further individuals from a consanguineous family with a homozygous PLOD3 c.809C>T; p.(Pro270Leu) variant. PLOD3 mRNA expression in the developing embryo was analysed for tissue-specific localisation. Mouse microarray expression data were assessed for phylogenetic gene expression similarities across CTDs with overlapping clinical features. Results: Key clinical features included ocular abnormalities with risk for retinal detachment, sensorineural hearing loss, reduced palmar creases, finger contractures, prominent knees, scoliosis, low bone mineral density, recognisable craniofacial dysmorphisms, developmental delay and risk for vascular dissection. Collated clinical features showed most overlap with Stickler syndrome with variable features of Ehlers-Danlos syndrome (EDS) and epidermolysis bullosa (EB). Human lysyl hydroxylase 3/ PLOD3 expression was localised to the developing cochlea, eyes, skin, forelimbs, heart and cartilage, mirroring the clinical phenotype of this disorder. Conclusion: These data are consistent with pathogenic variants in PLOD3 resulting in a clinically distinct Stickler-like syndrome with vascular complications and variable features of EDS and EB. Early identification of PLOD3 variants would improve monitoring for comorbidities and may avoid serious adverse ocular and vascular outcomes.